2019
DOI: 10.1088/1751-8121/ab56ed
|View full text |Cite
|
Sign up to set email alerts
|

A note on the double dual graviton

Abstract: The (free) graviton admits, in addition to the standard Pauli-Fierz description by means of a ranktwo symmetric tensor, a description in which one dualizes the corresponding (2, 2)-curvature tensor on one column to get a (D − 2, 2)-tensor, where D is the spacetime dimension. This tensor derives from a gauge field with mixed Yound symmetry (D − 3, 1) called the "dual graviton" field. The dual graviton field is related non-locally to the Pauli-Fierz field (even on-shell), in much the same way as a p-form potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Note also that in the absence of θ, the duality relation () becomes rather trivial, since the two would‐be dual gravitons are related algebraically rather than via a non‐local relation. This was observed and studied in [18]. However, a side result of our analysis is that in the presence of such a theta term, double duality does not lead to an algebraic relation between the two dual fields.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Note also that in the absence of θ, the duality relation () becomes rather trivial, since the two would‐be dual gravitons are related algebraically rather than via a non‐local relation. This was observed and studied in [18]. However, a side result of our analysis is that in the presence of such a theta term, double duality does not lead to an algebraic relation between the two dual fields.…”
Section: Introductionmentioning
confidence: 55%
“…We demonstrate that this can also be implemented off‐shell and discuss what is the meaning of the θ‐term in that case. Second, we discuss the “double” duality of gravitons in the presence of θ‐term and comment on how the results of [18] can be modified in that case. In the spirit of completeness, we start with a short review of graded geometry and how Fierz‐Pauli action looks like in this formulation.…”
Section: Duality For Gravitons In 4dmentioning
confidence: 99%
“…A first step towards this direction was made in [15], where all possible duals of differential forms were analysed on-shell and it was found that only a fraction of them are algebraically independent. This analysis is based on the preceding one for gravitons, which was performed in [16] and led to the result that the double dual of the graviton is not independent to the original field.…”
Section: Additional Results and Conclusionmentioning
confidence: 99%
“…In several other terms the inverse boxes will cancel as desired, but there will still be terms where the inverse boxes do not cancel. These will be of the general form 16) namely ones with multiple cross-contracted derivatives. Note also that this issue cannot be ameliorated by partial integration.…”
Section: Pos(corfu2019)138mentioning
confidence: 99%
“…Analogously, the one-form e ab decomposes as e ab μ ∶fe ðμνλÞ ; e ν νμ ; e μν;λ g; ð31Þ so that its trace e ν νμ corresponds to a spin-1 field, while the fully symmetric part e ðμνλÞ describes the highest spin field (s ¼ 3). The remaining field e μν;λ is of mixed (2,1) Young symmetry, remarkably coinciding with the dual of the graviton in five dimensions [77] (see also [78]). It is worth highlighting that in our context, the field e μν;λ is strictly required by hypersymmetry, instead of duality at the linearized level.…”
Section: A Action Principle and Local (Hyper)symmetriesmentioning
confidence: 90%